History of Ukraine: civilizational dimension : methodological recommendations for preparing for seminars and individual work for the course for international students of the first (bachelor's) level of higher education of the Medical Faculty, speciality "222 Medicine" [Electronic resource] - Бондаренко, Ганна Анатоліївна; Bondarenko, Hanna (Kharkiv : V. N. Karazin Kharkiv National University, 2025)
The methodological recommendations have been developed for international students tudyingin Ukrainianat the School of Medicine of V. N. Karazin Kharkiv National University. The manual provides essential directions for working with the course material, seminar plans with detailed methodological in structions for preparing for classes, as well as questions for self-assessment and final control. It also includes recommended literature, achronological table of key historical events, and a glossary. These methodological recommendations are intended for international students and for instructors who work with this category of learners.

Методичні рекомендації розроблено для іноземних студент здобувають освіту українською мовою на медичному факультеті Харківського національного університету імені В. Н. Каразіна. Посібник містить базові орієнтири для опрацювання навчального матеріалу, плани семінарських занять із докладними методичними вказівками щодо підготовки до них, запитання для самоперевірки знань та підсумкового контролю. Також подано рекомендовану літературу у хронологічну таблицю. Рекомендовано для іноземних студентів та викладачів, як працюють з цією категорією здобувачів освіти.
Історія України: цивілізаційний вимір : методичні рекомендації з підготовки до семінарських занять та виконання самостійної роботи з дисципліни для іноземних студентів першого (бакалаврського) рівня вищої освіти медичного факультету за спеціальністю «222 Медицина» [Електронний ресурс]
Електронне навчальне видання комбінованого використання. Можна використовувати в локальному та мережному режимі. В авторській редакції
Keywords: HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; SOCIAL SCIENCES::Social sciences::Education::Subject didactics; history of Ukraine; Ukrainian culture; civilizational dimension; cultural heritage; national identity; european context; historiography; periodization; intercultural dialogue; european integration; історія України; українська культура; цивілізаційний вимір; культурна спадщина; національна ідентичність; європейський контекст; історіографія; періодизація; міжкультурний діалог; європейська інтеграція